Phosphoproteomic Analysis of Haemaphysalis longicornis Saliva Reveals the Influential Contributions of Phosphoproteins to Blood-Feeding Success - Agwunobi, Desmond O.; Wang, Ningmei; Huang, Lei; Zhang, Yefei; Chang, Guomin; Wang, Kuang; Li, Mengxue; Wang, Hui; Liu, Jingze (Frontiers in Cellular and Infection Microbiology, 2022)
Tick saliva, an essential chemical secretion of the tick salivary gland, is indispensable for tick survival owing to the physiological influence it exerts on the host defence mechanisms via the instrumentality of its cocktail of pharmacologically active molecules (proteins and peptides). Much research about tick salivary proteome has been performed, but how most of the individual salivary proteins are utilized by ticks to facilitate blood acquisition and pathogen transmission is not yet fully understood. In addition, the phosphorylation of some proteins plays a decisive role in their function. However, due to the low phosphorylation level of protein, especially for a small amount of protein, it is more difficult to study phosphorylation. Maybe, for this reason, the scarcity of works on the phosphorylated tick salivary proteomes still abound. Here, we performed a phosphoproteomic analysis of Haemaphysalis longicornis tick saliva via TiO2 enrichment and the most advanced Thermo Fisher Orbitrap Exploris 480 mass spectrometer for identification. A total of 262 phosphorylated tick saliva proteins were identified and were subjected to functional annotation/enrichment analysis. Cellular and metabolic process terms accounted for the largest proportion of the saliva proteins, with the participation of these proteins in vital intracellular and extracellular transport-oriented processes such as vesicle-mediated transport, exocytic process, cell adhesion, and movement of cell/subcellular component. “Endocytosis”, “Protein processing in endoplasmic reticulum”, and “Purine metabolism” were the most significantly enriched pathways. The knockdown (RNAi) of Tudor domain-containing protein (TCP), actin-depolymerizing factors (ADF), programmed cell death protein (PD), and serine/threonine-protein kinase (SPK) resulted in the dissociation of collagen fibers and the pilosebaceous unit, increased inflammatory infiltrates/granulocytes (possibly heterophiles), and the depletion of the epithelium. Ticks injected with SPK dsRNA engorged normally but with a change in skin colour (possibly an autoimmune reaction) and the failure to produce eggs pointing to a possible role of SPK in reproduction and host immune modulation. Ticks injected with ADF dsRNA failed to acquire blood, underscoring the role of ADF in facilitating tick feeding. The results of this study showed the presence of phosphorylation in tick saliva and highlight the roles of salivary phosphoproteins in facilitating tick feeding.